2015
DOI: 10.1002/bdrb.21161
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Early Postnatal NSAID Treatment on Nephrogenesis in Wistar Rats

Abstract: A clinical Ibuprofen dose showed potential to inhibit kidney development in neonatal rats. FR did not modulate these effects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 27 publications
1
6
0
Order By: Relevance
“…Consistent with previous experimental data in human embryonic kidney (HEK) 293 cells, 69 ibuprofen‐triggered apoptosis in human fetal kidney explants, a phenomenon also reported in human fetal ovarian explants 60 . In newborn rats exposed to ibuprofen, an altered proliferation/apoptosis ratio associated with decreased nephrons counts was also described 15 . In addition, ibuprofen‐induced apoptosis clearly targets developing glomeruli as it does in the adult human kidney 70 .…”
Section: Discussionsupporting
confidence: 86%
“…Consistent with previous experimental data in human embryonic kidney (HEK) 293 cells, 69 ibuprofen‐triggered apoptosis in human fetal kidney explants, a phenomenon also reported in human fetal ovarian explants 60 . In newborn rats exposed to ibuprofen, an altered proliferation/apoptosis ratio associated with decreased nephrons counts was also described 15 . In addition, ibuprofen‐induced apoptosis clearly targets developing glomeruli as it does in the adult human kidney 70 .…”
Section: Discussionsupporting
confidence: 86%
“…16 According to several reports, IBU (on label intravenous dose of 10-5-5 mg/kg/day and PDA closure) exposure in preterm neonates results in transient reduction of urine output, a significant increase in sCr of up to 6 weeks after exposure and decreased drug clearance (À20%) for drugs cleared by glomerular filtration. [17][18][19] In addition to these short-term outcome observations in human neonates, animal experimental observations have been conducted on the reduction (from À7% to À12%) of glomerular number count in adult rodents 19 and on the reduction (À27%) of the renal cortex in adult primates after being exposed to IBU at a maturational age equivalent to extremely preterm human neonates. Although nephrotoxicity is lower than that of IND, short-term follow-up of renal function should also be performed when administering IBU for premature infants.…”
Section: Discussionmentioning
confidence: 99%
“…According to experimental evidence, another mechanism partially explains the differences in the effects of both drugs on regional circulations . According to several reports, IBU (on label intravenous dose of 10–5–5 mg/kg/day and PDA closure) exposure in preterm neonates results in transient reduction of urine output, a significant increase in sCr of up to 6 weeks after exposure and decreased drug clearance (−20%) for drugs cleared by glomerular filtration . In addition to these short‐term outcome observations in human neonates, animal experimental observations have been conducted on the reduction (from −7% to −12%) of glomerular number count in adult rodents and on the reduction (−27%) of the renal cortex in adult primates after being exposed to IBU at a maturational age equivalent to extremely preterm human neonates.…”
Section: Discussionmentioning
confidence: 99%
“…Our second aim was to evaluate whether extrauterine growth restriction could modulate the potential toxicity of drug treatment. Using the rat model of litter enlargement, we have previously shown that extrauterine growth restriction results in a reduction in nephron numbers (Bueters et al, , ). From the changes noted in body weight, it is clear that a state of extrauterine growth restriction was induced, even though body weights were slightly different from the start of the study.…”
Section: Discussionmentioning
confidence: 99%